The (null) effects of video questions on applicant reactions in asynchronous video interviews: Evidence from an actual hiring context - Nelli Niemitz; Lucas Rietheimer; Cornelius König; Markus Langer (International Journal of Selection and Assessment, 2024)
Asynchronous video interviews (AVIs) are growing in popularity, but tend to suffer from negative applicant reactions, possibly due to lower social presence compared to other interview formats. Research has suggested that specific design features may influence applicant reactions by increasing perceived social presence. In this study, we manipulated the question format (video vs. text) during an actual hiring process ( N 0.167em=0.167em76), testing whether video questions influence social presence, applicant reactions, impression management, and interview performance. There was no evidence that video (vs. text) questions affected any of these variables. We discuss how specific AVI design choices may have affected our results and suggest that future research could investigate the additive and interactive effects of different AVI design features.
Keywords: 650; applicant reaction; asynchronous video interviews; design features; media richness; social presence